Final Supplier Selection System in Military Critical Items - Nikou, Christodoulos; Moschuris, Socrates J. (SPOUDAI Journal of Economics and Business, 2012)
The financial plans of the Greek Ministry of Defense (MoD) for the year 2013 include a big amount of money in support of the national defense system. Nevertheless, comparing MoD’s annual budgets of the last two years, we can see that in 2013 less money than in 2012 were allocated to the MoD by the Government. This budgetary reduction could lead to the need for improvement in all phases of MoD’s function so that with limited resources, an even better result can be achieved. Supplier selection procedures could not be an exception, especially when it comes to critical supplies and services. Selecting Suppliers in military Critical Safety Items has multi-level features and many factors get involved. This paper develops a conceptual evaluation model based on Public Procurement Law in Defence (3978/2011), Analytic Hierarchy Process and Fuzzy Technique Order Performance by Similarity Ideal Solution. Multivariate Statistical Analysis (i.e. Principal Component Analysis, Factor Analysis and Cluster Analysis) and Quality tools are added to the model, while Business Intelligence/Competitive Intelligence is proposed as an additional tool to deal with the strong competitive environment of our days in a worldwide level. The use of Voronoi diagrams is also suggested as a technique that could affect criteria which are linked with the location of a potential supplier. We believe that the proposed model could end up in improving supplier selection procedures as it integrates contemporary approaches seen in the relevant academic literature with some of the particularities of the Armed Forces. JEL Classification: H56, H57, L39